Effect of bodybuilding athletes` weight loss method on performance factors and immune function - Kim, J.-H.; Kim, J.-S. (Journal of Exercise Rehabilitation, 2023)
This study was conducted on elite bodybuilders for 6 weeks using two weight loss methods (traditional method=high-weight loss vs. new method=low-weight loss). The subjects of this study were 26 male active elite bodybuilders who voluntarily wanted to participate in this experiment, and were divided into experimental group and traditional group. The traditional and experimental groups underwent dietary restrictions and training for 6 weeks. The conclusion obtained from the results of this study is that in the case of anthropometric variables, there is a difference in weight class between the two groups. The experimental group`s upper arm circumference was maintained compared to the pre-measured value after post-measurement, while the traditional group decreased, and a significant interaction effect was observed. In particular, a significant interaction effect was observed. In that the absolute value of maximum oxygen intake was significantly increased only in the post-experimental group compared to the pretest, and an interaction effect was observed, the use of low-weight loss method is more effective than the traditional method of high-weight loss method. An increase in some cytokines was observed despite traditional weight loss, but it did not cause an excessive decrease in immunity or a sharp decrease in performance factors. As a result of this experiment, it is judged that the use of a low-weight loss method is more preferable than the traditional high-weight loss method in relation to performance variables.